2020
DOI: 10.3389/fonc.2020.00872
|View full text |Cite|
|
Sign up to set email alerts
|

Radiomic-Based Quantitative CT Analysis of Pure Ground-Glass Nodules to Predict the Invasiveness of Lung Adenocarcinoma

Abstract: Objectives: To investigate the performance of radiomic-based quantitative analysis on CT images in predicting invasiveness of lung adenocarcinoma manifesting as pure ground-glass nodules (pGGNs). Methods: A total of 275 lung adenocarcinoma cases, with 322 pGGNs resected surgically and confirmed pathologically, from January 2015 to October 2017 were enrolled in this retrospective study. All nodules were split into training and test cohorts randomly with a ratio of 4:1 to estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 46 publications
4
29
1
Order By: Relevance
“…In our study, the predictive efficacy of the elected prognostic related radiomics features based on training set were found to be in accordance with some of the reference research above ( 30 , 33 , 34 , 36 ). However, a lot of former studies have concentrated on the performance of textural features of radiographic images, which may lack a comprehensive explanation of the biological mechanism and potential biomolecular features of the disease.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, the predictive efficacy of the elected prognostic related radiomics features based on training set were found to be in accordance with some of the reference research above ( 30 , 33 , 34 , 36 ). However, a lot of former studies have concentrated on the performance of textural features of radiographic images, which may lack a comprehensive explanation of the biological mechanism and potential biomolecular features of the disease.…”
Section: Discussionsupporting
confidence: 89%
“…Zhang et al [ 33 ] demonstrated that histogram parameters, combined with an evaluation of morphological characteristics, exhibited good diagnostic performances in discriminating AIS/MIA from IAC, appearing as pGGNs, The AUC, sensitivity and specificity of the predictive model was 0.896, 0.794, and 0.914, respectively. Similarly, for the prediction between AIS/MIA and IAC representing as pGGNs, Xu et al [ 34 ] showed the predictive radiomics models built in study (AUC 0.833;95% CI, 0.733–0.934) which provided a good predictive power. Besides, Sun et al [ 35 ] developed a radiomics-based Rad-score utilized as a biomarker for the invasiveness-predicted evaluation in patients with pGGNs (AUC 0.72; 95% CI, 0.63–0.81).…”
Section: Discussionmentioning
confidence: 93%
“…The number of patients/nodules ranged between 34/34 and 794/886. Eight studies [15,[17][18][19][20][21][22][23] included only mixed ground-glass nodules (MGGNs), seven [24][25][26][27][28][29][30] only pure ground-glass nodules (PGGNs), and thirteen [14,16,[31][32][33][34][35][36][37][38][39][40][41] both of MGGNs and PGGNs.…”
Section: General Characteristics Of Included Studiesmentioning
confidence: 99%
“…The ROIs were segmented manually in 20 studies [14,15,18,21,22,[24][25][26][27]29,[31][32][33][34][36][37][38][39][40][41], semi-automatically in six studies [17,19,20,28,30,35] and automatically in two studies [16,23] (Table 2). Multiple segmentations, more than one person segmented the ROIs, were conducted in 24 studies.…”
Section: Regions Of Interest (Rois) Segmentationmentioning
confidence: 99%
See 1 more Smart Citation